ETIKA BISNIS ISLAM - Budi Februari; Husnul Khatimah; Afiyah Dwi Astri; Dini Vientiany (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study discusses Islamic business ethics as a moral guide in business practices based on sharia principles. This study uses a qualitative method with a library research approach, collecting data from literature such as books and scientific articles. The focus of the study is to identify and analyze the principles of Islamic business ethics, including the prohibition of usury (interest), gharar (uncertainty), and the application of honesty and justice. The results of the analysis show that Islamic business ethics are not only oriented towards material gain, but also towards social responsibility and the welfare of the people. This study aims to provide insight into the application of business ethics in the context of sharia and encourage business actors to carry out practices that are in line with Islamic values.